KOMPETENSI, KEPEMIMPINAN, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN HUMAN RESOURCES AND FACILTY MANAGEMENT DIRECTORATE - SETIA TJAHYANTI; NURAFNI CHAIRUNNISA (Media Bisnis, 2020)
The purpose of this study was to determine the effect of several variables such as competence, leadership, and work discipline on employee performance. The method used is descriptive and causality. The statistical test in this study uses Multiple Regression Analysis. Respondents involved in this study were 82 employees who were permanent employees at the Human Resources and Facility Management Directorate at PT Gramedia Asri Media, Jakarta Head Office. The sampling method of this research is using purposive sampling. Data collection techniques using questionnaires and interviews. Data analysis was performed using multipleregression. The results showed that partially competence has an effect on employee performance, leadership does not affect employee performance, work discipline affects employee performance.